The Frequent Sampling of Wound Scratch Assay Reveals the “Opportunity” Window for Quantitative Evaluation of Cell Motility-Impeding Drugs - Kauanova, Sholpan; Urazbayev, Arshat; Vorobjev, Ivan (Frontiers in Cell and Developmental Biology, 2021)
Wound healing assay performed with automated microscopy is widely used in drug testing, cancer cell analysis, and similar approaches. It is easy to perform and results are reproducible. However, it is usually used as a semi-quantitative approach, because of inefficient image segmentation in transmitted light microscopy. Recently several algorithms for wound healing quantification were suggested, but none of them was tested on a large dataset. In the current study, we develop a pipeline allowing to achieve correct segmentation of the wound edges in >95% of pictures and extended statistical data processing to eliminate errors of cell culture artifacts. Using this tool, we collected data on wound healing dynamics of 10 tissue cultures with 10 minutes time resolution. We determine that the overall kinetics of wound healing is non-linear, however, all cell lines demonstrate linear wound closure dynamics in a 6-hour window between 5-th and 12-th hours after scratching. We next analyzed microtubule inhibiting drugs, nocodazole, vinorelbine, and Taxol action on the kinetics of wound healing in the drug concentration-dependent way. Within this time window, the measurements of the velocity of the cell edge allow detection of statistically significant data when changes did not exceed 10-15%. All cell lines show a decrease of the wound healing velocity at millimolar concentrations of microtubule inhibitors. However, the dose-dependent response was cell line-specific and drug-specific. Cell motility was completely inhibited (edge velocity decreased 100%), while in others it decreased only slightly (not more than 50%). Nanomolar doses (10-100 nM) of microtubule inhibitors in some cases even elevated cell motility. We speculate that anti-microtubule drugs might have specific effects on cell motility not related to the inhibition of the dynamic instability of microtubules.